Off-line keyword guessing attacks on recent Public Key Encryption with Keyword Search Schemes - Wei-Chuen, Yau; Swee-Huay, Heng; Bok-Min, Goi (SPRINGER-VERLAG BERLIN, 2008)
The Public Key Encryption with Keyword Search Scheme (PEKS) was first proposed by Boneh et al. in 2004. This scheme solves the problem of searching on data that is encrypted using a public key setting. Recently, Back et al. proposed a Secure Channel Free Public Key Encryption with Keyword Search (SCF-PEKS) scheme that removes the secure channel for sending trapdoors. They later proposed another improved PEKS scheme that integrates with a public key encryption (PKE) scheme, called PKE/PEKS. In this paper, we present off-line keyword guessing attacks on SCF-PEKS and PKE/PEKS schemes. We demonstrate that outsider adversaries that capture the trapdoors sent in a public channel can reveal encrypted keywords by performing off-line keyword guessing attacks. While, insider adversaries can perform the attacks regardless the trapdoors sent in a public or secure channel.